WBRT vs. APBI: an interim report of patient satisfaction and outcomes - Bitter, Samantha M.; Heffron-Cartwright, Patricia; Wennerstrom, Christopher; Weatherford, Jared; Einstein, Douglas; Keiler, Louis C. (Journal of Contemporary Brachytherapy, 2016)
Purpose : To determine differences in patient’s reported quality of life and self-reported breast cosmesis between whole breast radiation therapy (WBRT) and accelerated partial breast irradiation (APBI) via single and multi-lumen high-dose-rate (HDR) brachytherapy for women with early stage breast cancer. Material and methods: Patient information was retrospectively reviewed and survey data were prospectively collected for women treated between 2004 to 2014 (APBI) and 2012 to 2014 (WBRT). Criteria for APBI treatments were ER+ (after 2010), N0 (after 2010), T < 3 cm, and post-menopausal. All patients were given a survey with modified FACIT (Functional Assessment of Chronic Illness Therapy) breast quality of life questions to rate their amount of pain, self-consciousness, low energy, presence of lymphedema, and breast cosmesis. Results : 242 APBI patients and 59 WBRT patients were identified. In the WBRT cohort, 34 women met departmental criteria for APBI treatment (WBRT who were APBI eligible). The FACIT survey was completed by 80 women treated with APBI (33%; mean follow-up time of 14 months), and 26 women treated with WBRT who were APBI eligible (76%; mean follow-up time of 26 months). During the first year post-treatment, low energy (p = 0.009), self-consciousness (p = 0.0004), and lymphedema (p = 0.0002) scores were significantly lower in the APBI cohort when compared to women treated with WBRT who were APBI eligible. During the second year post-treatment, women treated with APBI reported significantly better breast cosmesis (p = 0.04). The single-lumen balloon (score = 6.3/10) was found to be associated with worse cosmesis compared to the multi-lumen balloons (Mammosite ML and Contura; score = 8.2/10; p = 0.002). There were no significant differences in rates of recurrence between balloons or treatments (p > 0.05). Conclusions : APBI treated patients reported higher cosmetic satisfaction than patients in the matched WBRT cohort. Quality of life scores tended to improve over time. Multi-lumen catheters provided superior cosmetic results compared to single-lumen catheters.